The study of phytophthora heart rot disease of pineapple in some selected districts in the Central Region - Amoateng, Amma Kissiwaa (University of Cape Coast, 2021)
Phytophthora heart rot disease (PHRD) of pineapple is one of the damaging diseases that attack pineapple plants of all ages and can cause 100% yield loss. Documented information on the disease in Ghana is quite limiting even though Ghana is among the top exporting countries in Africa. It is therefore essential to know the status of this disease, the particular species of Phytophthora causing the disease in the selected areas of study (Komenda-Edina-Eguafo- Abrem, Abura-Asebu-Kwamankese and Ekumfi districts) and how it could be managed using botanicals and bio-control organism. The study was conducted in three main phases: surveys (demographic and field), pathogen identification and characterisation and in vitro disease management. One hundred and twenty (120) farmers were interviewed using structured questionnaires. The disease was present in seven (7) out of the twelve (12) communities selected for the survey. The highest incidence was recorded at Abrenu-Akyinim (3.40%) and Asofa (3.40%) with the least at Nanaben (0.4%). Disease severity was highest at Abrenu-Akyinim (1.50) and lowest at Atabadze (0.2). P. nicotiannae and P. cinnamomi were both found to be the causative organism of PHRD in the study area. In vitro control studies using Neem, Prekԑsԑ, Mahogany extract and Trichoderma asperellum via Minimum Inhibitory Concentration test showed that all treatments with the exception of Mahogany were inhibitory to P. cinnamomi with Prekԑsԑ recording the highest mean inhibition index of 3.00. A dual culture technique test performed using the Trichoderma sp. and Phytophthora isolates on different application days, showed that, the application of the Trichoderma 24 hrs before plating the isolate gave the highest inhibition percentage.
xi,132p:,ill.
Keywords: Ananas comosus (Pineapple); Bio-control; Botanicals; Central region; Phytophthora spp; Heart rot disease